Keli M. Mažvydo raštų žodžių darybos bruožai istoriniu požiūriu - Ambrazas, Saulius (Baltistica, 1997)
SOME DERIVATIVE FEATURES IN THE WRITINGS BY M. MAŽVYDAS FROM THE DIACHRONIC POINT OF VIEWSOME DERIVATIVE FEATURES IN THE WRITINGS BY M. MAŽVYDAS FROM THE DIACHRONIC POINT OF VIEWThe data, observed in the writings by M. Mažvydas and other old Lithuanian texts, let us to distinguish some derivative isoglosses in the Old Lithuanian dialects of the 16th–17th centuries: 1. archaic nomina agentis with the suffix -tojas from primary verbs (cf. apgintojas ‘protector’) were widely used in Low Lithuanian and in the High Lituanian dialect of East Prussia; 2. the suffix -inykas (-ė), instead of -ininkas (-ė), was still used in Low Lithuanian; 3. the suffix -ybė played the main role in the formation of nomina qualitatis in the Low and High East Lituanian dialects;. nomina qualitatis with the suffix -imas / -ymas still preserved an abstract meaning in the texts by M. Mažvydas (cf. sveikimas ‘healthiness’ 713 ); 5. nomina actionis on -aujimas was characteristic feature of Low Lithuanian and the West High Lithuanian dialect of East Prussia (cf. paliaujimas ‘cessation’).
Keywords: lithuanian; old writings; Mažvydas; word formation